O Programa Bolsa Família, suas condicionalidades na educação e seu efeito protetivo para adolescentes em conflito com a lei - Nivia Soares da Silva (2015)
Poverty, inequality, social exclusion and violence practiced by teens are a subject of concern in the contemporary world, as it can be evidenced by the attention that it has deserved in scientific studies. The present study has the purpose of analyzing the Bolsa Família Program (Family Allowance Program) and its influence on the offending conduct of adolescents rendering Community Service, in Belo Horizonte. For such, the database of the Cadastro Único (Single Registry) of the federal government, the Sistema Presença (School Attendance System) of the Ministry of Education, and the Sistema de Informações Gerenciais das Políticas Sociais (Social Policy Management Information System) of Belo Horizonte municipal government has been used. The main interest was to describe the socioeconomic, ethnical, spatial and school profile of adolescents from families participating in the Program, in Belo Horizonte; describe the socioeconomic, ethnical and spatial profile of adolescents serving assisted freedom socio-educational measure; compare sociodemographic profiles of adolescent groups of the Cadastro Único (Single Registry) - active and inactive in Bolsa Família Program (Family Allowance Program) - and their situation of being or not in compliance with socio-educational measures; examine the association between the fulfillment of education conditionality of the Bolsa Família Program, and the fulfillment of socio-educational measure of the Community Service Provision (Portuguese acronym PSC), that is, whether the effects of the school attendance conditionality of the Bolsa Família fall upon the fulfillment of the social- educational measures. A descriptive statistic has been carried out with crossed and simple frequency distribution. In addition, a multivariate correspondence analysis has been carried out. The results have shown that the average per capita income of those active participants of the Family Allowance Program is lower and more homogenous than the average income of those nonactive participants. More than half of the active participants in the program are dark skinned and present a higher percentage of school attendance. Concerning the adolescents in PSC, it has been observed that the completion of the socioeducational measure is higher among those active participants in the Program. It was found that active adolescents in the Bolsa Família have a higher percentage of school attendance in relation to active adolescents and in Community Service Provision. It has also been noted that the African descendant adolescents and those in PSC are more associated to lower incomes. And, if that adolescent is not in the PSC, there is a slight higher association for the per capita income range from R$ 77,00 to R$ 154,00. Adolescents who have declared themselves white are more associated with higher per capita ranges, and of those, the ones who are in the PSC have been more associated with per capita income ranges from R$ 77,00 to R$ 154,00. Conclusion: These data suggest that the Bolsa Família Program, to meet priority adolescents coming from lower income families and groups that are in a position to latent social inequality in terms of broader racial issues, if effective appropriately to mission of conditional cash transfer programs, to which it belongs.